Prognostic value of echocardiographic and Doppler parameters in horses admitted for colic complicated by systemic inflammatory response syndrome. (1st April 2014) - Borde, Laura; Amory, Hélène; Grulke, Sigrid; Leroux, Aurélia A.; Houben, Rosa M.; Detilleux, Johanne; Sandersen, Charlotte C.
Abstract Objective To assess the prognostic value of echocardiographic parameters of left ventricular (LV) function in horses with systemic inflammatory response syndrome (SIRS). Design Prospective observational study. Setting Veterinary teaching hospital. Animals Forty‐one horses admitted for colic with clinical evidence of SIRS. Interventions All horses underwent Doppler echocardiographic examination on admission. LV echocardiographic parameters, including pulsed‐wave tissue Doppler imaging parameters, were compared between nonsurvivors (n = 29) and horses that survived to discharge (n = 12). Measurements and Main Results With comparable heart rate and LV preload estimate, LV stroke volume index, the velocity time integral, deceleration time, ejection time of Doppler aortic flow, and peak early diastolic myocardial velocity were lower in the nonsurviving than in the surviving horses, while pre‐ejection period to ejection time ratio (PEP/ET) of Doppler aortic flow and the peak early diastolic filling velocity to peak early diastolic myocardial velocity ratio (E/Em) were higher (P < 0.05). A cut‐off value of 0.26 for PEP/ET predicted mortality with 100% sensitivity and 42% specificity (area under the receiver operating characteristic curve: 0.71), whereas a cut‐off value of 2.67 for E/Em predicted mortality with 100% sensitivity and 83% specificity (area under the receiver operating characteristic curve: 0.89). Conclusions Echocardiography may provide prognostic information in colic horses with clinical evidence of SIRS. Especially, PEP/ET and E/Em could be useful markers of systolic and diastolic dysfunction, respectively, to detect horses with a high risk of death requiring more intensive cardiovascular monitoring as it has been reported in human patients with septic shock.